Nuclear DBF-2-related Kinases Are Essential Regulators of Cytokinesis in Bloodstream Stage Trypanosoma brucei - Ma, Jiangtao (American Society for Biochemistry and Molecular Biology, 2010)
Nuclear DBF-2-related (NDR) kinases are essential regulators of cell cycle progression, growth, and development in many organisms and are activated by the binding of an Mps One Binder (MOB) protein partner, autophosphorylation, and phosphorylation by an upstream STE20 family kinase. In the protozoan parasite, Trypanosoma brucei, the causative agent of human African trypanosomiasis, the NDR kinase, PK50, is expressed in proliferative life cycle stages and was shown to complement a yeast NDR kinase mutant cell line. However, the function of PK50 and a second NDR kinase, PK53, in T. brucei has not been determined to date, although trypanosome MOB1 is known to be essential for cytokinesis, suggesting the NDR kinases may also be involved in this process. Here, we show that specific depletion of PK50 or PK53 from bloodstream stage trypanosomes resulted in the rapid accumulation of cells with two nuclei and two kinetoplasts, indicating that cytokinesis was specifically inhibited. This led to a deregulation of the cell cycle and cell death and provides genetic validation of these kinases as potential novel drug targets for human African trypanosomiasis. Recombinant active PK50 and PK53 were produced and biochemically characterized. Both enzymes autophosphorylated, were able to trans-phosphorylate generic kinase substrates in vitro, and were active in the absence of phosphorylation by an upstream kinase. Additionally, both enzymes were active in the absence of MOB1 binding, which was also demonstrated to likely be a feature of the kinases in vivo. Biochemical characterization of recombinant PK50 and PK53 has revealed key kinetic differences between them, and the identification of in vitro peptide substrates in this study paves the way for high throughput inhibitor screening of these kinases.